Fluoroscopic confirmation of needle location in ultrasound-guided genicular nerve radiofrequency thermocoagulation - KOKAR, SERDAR (My University, 2023)
BACKGROUND: Radiofrequency thermocoagulation of genicular nerves is an effective treatment for chronic pain due to knee osteoarthritis. The procedure can be performed under fluoroscopic or ultrasonographic guidance. OBJECTIVES: The aim of this study was to fluoroscopically check the final location of the needle in ultrasound-guided genicular nerve radiofrequency thermocoagulation and evaluate the treatment\"s success in patients with knee pain. STUDY DESIGN: A 2-center, prospective study. SETTING: A private clinic and a tertiary care health center. METHODS: Thirty-two patients who had unilateral knee pain, and grade 3-4 knee osteoarthritis according to the Kellgren-Lawrence classification were included. Following diagnostic genicular nerve blocks in patients whose knee pain was relieved by >= 50%, radiofrequency thermocoagulation was applied to these nerves. The final position of the needle was checked via fluoroscopy in anteroposterior and lateral planes. RESULTS: The needle was located in the one-third anterior portion of the bone shaft in 69 of 96 patients (71.9%), between one-third and two-thirds in 21 (21.9%), and in the one-third posterior portion in 6 (6.3%). The mean Numeric Rating Scale score for pain was 7.69 ± 0.99 before treatment, 4.03 ± 1.26 at one week, 2.53 ± 1.24 at one month, and 2.19 ± 1.71 at 3 months, indicating a statistically significant decrease (P < 0.001). LIMITATIONS: The lack of a study group in which genicular nerve radiofrequency thermocoagulation was performed under fluoroscopy guidance could be cited among the limitations of this clinical study. CONCLUSIONS: The final position of the needle tip in radiofrequency thermocoagulation of genicular nerves can exist at the one-third anterior of the bone shaft, without a need for further advancing the needle to the posterior portion. Although performed more distally compared to fluoroscopy guidance, ultrasound-guided genicular nerve radiofrequency thermocoagulation still provides effective analgesia.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ANESTEZİYOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ANESTHESIOLOGY; Anesteziyoloji ve Ağrı Tıbbı; Anesthesiology and Pain Medicine; fluoroscopy; interventional ultrasonography; knee osteoarthritis; pain management; radiofrequency ablation; Genicular nerve